A statistic study of ionospheric solar flare activity indicator. Issue 1 (9th January 2014) - Xiong, Bo; Wan, Weixing; Ning, Baiqi; Ding, Feng; Hu, Lianhuan; Yu, You
Abstract According to the Chapman ionization theory, an ionospheric solar flare activity indicator (ISFAI) is given by the solar zenith angle and the variation rate of ionospheric vertical total electron content, which is measured from a global network of dual‐frequency GPS receivers. The ISFAI is utilized to statistically analyze the ionospheric responses to 1439 M‐class and 126 X‐class solar flares during solar cycle 23 (1996–2008). The statistical results show that the occurrence of ISFAI peak increases obviously at 3.2 total electron content unit (TECU)/h (1 TECU = 1016 el m−2) and reaches the maximum at 10 TECU/h during M‐class flares and 10 TECU/h and 40 TECU/h for X‐class flares. ISFAI is closely correlated with the 26–34 nm extreme ultraviolet flux but poorly related to the 0.1–0.8 nm X‐ray flux. The central meridian distance (CMD) of flare location is an important reason for depressing relationship between ISFAI and X‐ray Flux. Through the CMD effect modification, the ISFAI has a significant dependence on the X‐ray flux with a correlation coefficient of 0.76. The ISFAI sensitivity enables to detect the extreme X‐class flares, as well as the variations of one order of magnitude or even smaller (such as for C‐class flares). Meanwhile, ISFAI is helpful to the calibration of the X‐ray flux at 0.1–0.8 nm observed by GOES during some flares. In addition, the statistical results demonstrate that ISFAI can detect 80% of all M‐class flares and 92% for all X‐class ones during 1996–2008.